Electron-Microscopic Investigation of Interactions between Yersinia pseudotuberculosis, Yersinia pestis Cells and Specific Bacteriophages - A. V. Chernyad’Ev; L. G. Dudina; S. G. Litvinets; V. P. Chernikov; A. A. Byvalov (Проблемы особо опасных инфекций, 2014)
Carried out has been electron-microscopic investigation of dynamics of interactions between Yersinia pseudotuberculosis, Yersinia pestis cells and specific bacteriophages in vitro. Identified have been peculiarities in morphological manifestation of the interactions. Determined are morphometric characteristics of the bacteriophages utilized in the experiment. It is demonstrated that after 40 minutes of co-incubation of Y. pseudotuberculosis with specific bacteriophage emergence of persisting forms of microbial cells is observed, while in case of EV strain infecting with Pokrovskaya bacteriophage, this phenomenon is not detected.